Evaluation of functional resilience in urban drainage and flood management systems using a global analysis approach - Mugume, Seith N.; Butler, David (Urban Water Journal, 2017)
Enhancing resilience in urban drainage systems (UDSs) requires new evaluation approaches that explicitly consider vital interactions between threats, system performance and resulting failure impacts during both normal and unexpected (exceptional) loading conditions. However, current reliability-based approaches only focus on prevention of functional (hydraulic) failures resulting from a specified design storm. In this study, the global resilience analysis (GRA) approach is further extended for evaluation of UDS performance when subject to a wide range of random functional failure scenarios (extreme rainfall) with varying magnitude, duration, and spatial distribution. The resulting loss of system functionality during the simulated failure scenarios is quantified using total flood volume and mean flood duration. System residual functionality for each considered rainfall block loading scenario is quantified using the functional resilience index. The developed approach has been successfully applied to test and characterise the functional resilience to extreme rainfall of an existing UDS in Kampala city, Uganda. The study concluded that: (1) UDS functional resilience is significantly influenced by both occurrence of short duration, high intensity rainfall events and spatial rainfall variation during extreme rainfall conditions and (2) future planning and design of resilience enhancement strategies should apply spatially distributed rainfall inputs to facilitate effective sizing of potential adaptation strategies.
Keywords: Global resilience analysis; hydraulic failures; pluvial flooding; spatial rainfall distribution